2009
DOI: 10.1590/s1516-635x2009000200003
|View full text |Cite
|
Sign up to set email alerts
|

Calcium levels and limestone particle size in the diet of commercial layers at the end of the first production cycle

Abstract: This study evaluated the effect of dietary calcium levels and limestone particle size distribution on first-cycle layer performance and egg quality. A completely randomized experimental design in 4x3 factorial arrangement (four Ca levels -3.0, 3.5, 4.0, 4.5%; and three limestone particle size distributions -100% fine, 50% fine and 50% coarse, 30% fine and 70% coarse) was applied, totaling 12 treatments with six replicates of eight birds each. The treatments did not influence the most of evaluated performance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 16 publications
7
21
3
2
Order By: Relevance
“…Similar results were observed by Vieira et al (2011), when evaluating the calcium levels of 28, 33 and 38 g/kg in the diet of brown egg layers from 40 weeks of age, and by Pelícia (2009b), in an experiment with brown egg layers in the period from 59 to 70 weeks of age fed diets containing the calcium levels of 30, 35, 40 and 45 g/kg. These authors verified increase in the calcium excretion, in g/bird/day and in g/kg, respectively, and attributed this result to the concentration of calcium in the diet.…”
Section: Resultssupporting
confidence: 80%
“…Similar results were observed by Vieira et al (2011), when evaluating the calcium levels of 28, 33 and 38 g/kg in the diet of brown egg layers from 40 weeks of age, and by Pelícia (2009b), in an experiment with brown egg layers in the period from 59 to 70 weeks of age fed diets containing the calcium levels of 30, 35, 40 and 45 g/kg. These authors verified increase in the calcium excretion, in g/bird/day and in g/kg, respectively, and attributed this result to the concentration of calcium in the diet.…”
Section: Resultssupporting
confidence: 80%
“…Similarly, Cufadar et al (2011) found no differences in egg production, egg weight, egg mass, feed intake and feed conversion ratio when moulted layers were fed diets with 3.0, 3.6 or 4.2 % of Ca. Pelicia et al (2009) reported that increasing dietary levels of Ca (3.00-4.50 %) did not influence laying performance in hens at the end of the production cycle (58 to 70 weeks of age). In contrast, Saafa et al (2008) showed that, late in the production cycle (58 to 73 weeks of age), hens require more than 3.5 % of Ca in the diet for optimal laying performance, since an increase in Ca dietary levels to 4.0 % improved egg production, egg mass and the feed conversion ratio.…”
Section: Laying Performancementioning
confidence: 97%
“…its utilization (Pizzolante et al, 2009). Other studies showed that large particle sizes have no effect on shell quality, even when calcium levels in the diet are adequate (Pelicia et al, 2009;Pizzolante et al, 2009;Saunders-Blade et al, 2009). Frequently, the results of research show that artificial lighting programs influence egg production, but not egg quality parameters (Jácome et al, 2014).…”
Section: Resultsmentioning
confidence: 99%